Multiple Organ Maintenance/Replacement Therapy - A. F. Yampolsky (Общая реаниматология, 2008)
The paper reviews data on novel and combined maintenance/replacement therapies used to treat multiple organ failure/dysfunction, including those of septic origin. The basis of using these treatments is a new ideology of applying the earlier known and newly developed methods of efferent therapy that substantially improves the results of treatment in most seriously ill patients at intensive care units.